Motivos que levam as instituições financeiras brasileiras a deixarem de utilizar a opção do Hedge Accounting - Amaral, Rodrigo Selingardi do (2020)
The main objective of this research is to identify the reasons that are capable of influencing and leading Brazilian banks not to classify their derivative protection instruments (Economic Hedge) as Hedge Accounting. An exploratory qualitative research was carried out through semi-structured interviews with content analysis with people groups from financial institutions in segments S1 and S3 (BACEN criteria), external consulting companies and external audit. As a result of this research, it was identified that the factors that hinder the implementation of Hedge Accounting operations are the difficulty of S3-sized banks in relation to S1-sized banks in the processes of understanding the accounting standards related to Hedge Accounting and effectiveness testing procedures as well as the perception of cost and benefit of the tool in the company's accounting decisions. As practical implications of this work, it can be mentioned that the research was limited to validating the existing problems by conducting individual interviews, therefore it is not free from specific situations experienced and reported by the interviewees. As an academic contribution, the theories of disclosure and institutional theory related to aspects of influence on accounting decision-making will be reviewed.